The Trauma of Peer Abuse: Effects of Relational Peer Victimization and Social Anxiety Disorder on Physiological and Affective Reactions to Social Exclusion - Iffland, Benjamin; Sansen, Lisa M.; Catani, Claudia; Neuner, Frank (Frontiers in Psychiatry, 2014)
Background: Social exclusion elicits emotional distress, negative mood and physiological stress. Recent studies showed that these effects were more intense and persisting in socially anxious subjects. The present study examined whether the abnormal reactions of socially anxious subjects can be traced back to previous experiences of relational peer victimization during childhood and adolescence. Methods: Participants (N = 74) were patients with a diagnosis of social anxiety disorder as well as healthy controls. The patient and control groups were subdivided into two subgroups according to the subject’s reports about previous relational peer victimization. Immediate and delayed physiological (skin conductance level and heart rate) and affective reactions to a simulated social exclusion in a ball-toss game (Cyberball) were recorded. Results: Overall, subjects’ immediate reactions to social exclusion were an increase in skin conductance and a reduction of positive affect. Regardless of the diagnostic status, subjects with a history of relational peer victimization showed a more intense self-reported affective change that was accompanied by a blunted skin conductance response. However, the mood of the subjects with a history of peer victimization recovered during a 15 min waiting period. A diagnosis of social anxiety disorder did not affect the reactions to social exclusion on any measure. Conclusions: Findings indicate that stress reactions to social exclusion depend more on previous experiences of peer victimization than on a diagnosis of social anxiety disorder. The findings indicate that memories of negative social experiences can determine the initial stress reaction to social threats.